Efektivitas Kayu Secang (Caesalpina sappan L.) dalam Menurunkan Bakteri Coliform pada Air Minum Isi Ulang - Khiki Purnawati Kasim; Rafidah Rafidah; Rostina Rostina; Nurkhatimah Latifah (Direktorat Politeknik Kesehatan Makassar, 2024)
Diarrhea in Indonesia is still a problem with high morbidity and mortality rates. Factors that influence the prevalence of this disease are that some people in Indonesia do not have access to healthy drinking water and proper sanitation. The quality of drinking water that does not meet bacteriological requirements can be a cause of diarrheal disease. So it needs to be anticipated through concrete steps by utilizing natural resources that contain anti-microbial compounds such as flavonoids, tannins, brazilin and brazilein which function as anti-microbials. The purpose of this study was to determine the effectiveness of Secang Wood (Caesalpinia Sappan L.) in reducing bacteria Coliform in Refillable Drinking Water with experimental research methods quasi laboratory scale by using 1 gram of secang wood in 1 liter of refillable drinking water with a variation of contact time 12 hours, 24 hours, and 36 hours.The results of the study of the addition of 1 gram of secang wood in 1 liter of refillable drinking water with a contact time of 12 hours the percentage of decrease is 100%, 24 hours the percentage of decrease is 100% and 36 hours the percentage of decrease is 100%. Based on the results obtained from the three observations, the results of the quality of pH, color, and turbidity examination were best at a contact time of 12 hours compared to the contact time at 24 hours and 36 hours. The addition of secang wood with a contact time of 12 hours, 24 hours and 36 hours is effective in reducing bacteriaColiform bacteria in accordance with the requirements of Permenkes RI No. 2 Year 2023. For this reason, it is recommended for the community to use secang wood with a contact time of 12 hours in drinking water as an effort to prevent diarrheal disease. Keywords :Coliform; secang wood(Caesalpinia Sappan L.); refillable drinking water